PENINGKATAN KETERAMPILAN MENULIS PARAGRAF MELALUI MEDIA PUZZLE PADA SISWA KELAS III SD N REJOWINANGUN 1 YOGYAKARTA - Intan nur Fitriyani; Siti Anafiah (Universitas Sarjanawiyata Tamansiswa, 2017)
This research was aimed at describing the improvement of skill in writing paragraph using puzzle for students of grade III at SD Negeri Rejowinangun 1 Yogyakarta. The type of this research was Classroom Action Research (CAR) which was conducted in two cycles. The result of this research showed that by using puzzle as the media could improve the skill in writing paragraph for students in class IIIA at SD Negeri Rejowinangun 1 Yogyakarta. The students’ mean score obtained in the pre-test was 65,08 and increased into 78,4 in the post-test of Cycle I and then become 83,16 in the post-test of Cycle II. Based on the result of the research above, it could be concluded that the use of puzzle as the media could improve third grade students’ skill in writing paragraphs at SD Negeri Rejowinangun 1 Yogyakarta.